Псевдоожиженный слой катализатора как пламегасящий элемент - Тюльпинов, Д. А.; Суворин, А. В. (НТУ "ХПИ", 2006)
Досліджено розповсюдження полум'я в псевдозріджений шар інертного і каталітично активного зернистого матеріалу. Встановлені принципові відмінності. Глибина проникнення полум'я в псевдозріджений шар на декілька порядків більше, ніж в стаціонарний. Каталітично активний шар при підвищених температурах більш ефективно, ніж інертний локалізує полум'я, а досягши робочої температури каталізатора гасить його. Запропонований спосіб гасіння полум'я без переривання потоку в вогнепереградачу з псевдозрідженим шаром каталізатора.

Distribution of flame into the fluidized layer of inert and catalytically active grainy material is explored. The principle distinctions are established. The depth of penetration of flame into a fluidized layer on a few orders is more than in stationary one. Catalytically active layer at the promoted temperatures is more effective, than the inert localizes flame, and under reaching the working temperature of catalyst extinguishes it. The method of flame extinguishing without breaking of stream in flame arresters with the fluidized layer of catalyst is offered.
Keywords: огнепреградители; пылегазовые смеси; псевдоожиженная насадка; каталитическое окисление; гетерогенная реакция